Pengaruh Total Hutang, Modal Kerja Dan Penjualan Terhadap Laba Pada Perusahaan Hotel, Restoran Dan Pariwisata Yang Terdaftar Di Bursa Efek Indonesia - H, Masliannur.; Harmain, Hendra; Harahap, Rahmat Daim (LPPM Universitas Labuhanbatu, 2022)
This study aims to determine the effect of total debt, working capital and sales on profits in hotel, restaurant and tourism companies listed on the Indonesian stock exchange. This research is a research that uses secondary data in the form of an annual report which is accessed through www.idx.co.id. The method used is purposive sampling method. The data analysis technique used is panel data regression analysis with Fixed Effect Model estimation which is tested using Eviews version 9. The results show that first, total debt has a negative effect on company profits, this means that total debt is one of the factors in increasing or decreasing profits. produced by the company every year. Second, working capital has a positive effect on company profits, this means that working capital is funds that have been used to finance company operations to earn profits. Third, sales have no effect on profit, this means that the size of the profit earned by the company in a certain period is not influenced by the size of the level of sales successfully carried out by the company. Fourth, total debt, working capital and sales affect the company's profit, so that together the high and low independent variables can affect the size of the company's profit. The value of the R-Square coefficient in this study is 0.7746 which means that the total debt, working capital and sales variables are able to affect profits by 77.46%, while the remaining 22.54% is influenced by variables outside the study.